BIOFLAVONOIDS WITH ANTICANCER ACTIVITY AND THEIR NOVEL FORMULATIONS - J, Padmavathy (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Context: Nature blesses human with a lot of natural products with a wide range of medicinal properties from plants, animals, marine animals, and microorganisms. Among these natural sources, plant origin drugs constitute around 25% which includes various secondary metabolites such as alkaloids, bioflavonoids, terpenes, saponins, glucosides, and lignans. The bioflavonoids belonging to the polyphenol group possess various therapeutic activities such as antioxidant, hepatoprotective, antibacterial, anti-inflammatory, anticancer, and antiviral. Objectives: The main objective of this article is to collectively present the research data published worldwide about the anticancer activity of bioflavonoids by loading them in novel formulations. Thus, the present review explored the novel formulations of the bioflavonoids with improved pharmacokinetic properties along with the enhanced anticancer activity. Methods: A systematic scientific review was made across the peer-reviewed scientific journals and books to collect the data pertaining to areas research related to the application of bioflavonoids for treatment of cancer using novel pharmaceutical formulations. Results: The major drawback with bioflavonoids is its poor solubility and bioavailability, which restricts the usage of bioflavonoids in the treatment of cancer in the market worldwide. Novel drug delivery system seems to possess many benefits like site-specific drug delivery along with minimal side effects and improving its pharmaceutical and therapeutic properties of drugs compared to a conventional dosage form of bioflavonoids. Conclusion: The scope for improvement of anticancer activity of bioflavonoids by incorporating in novel pharmaceutical formulations like nanoparticles is very high, and it has to be considered as a potential area of research.